2017
DOI: 10.1016/j.ijsu.2017.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic near-infrared fluorescent imaging as an alternative option for sentinel lymph node mapping in endometrial cancer: A prospective study

Abstract: Sentinel lymph node mapping can easily be performed with high accuracy by using NIR/ICG integrated conventional laparoscopic system in endometrial cancer and almost all lymphatic spread can be detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…However, it was not possible to reach higher numbers of such a specific condition with approximately 20% prevalence 3,4,7 in this single-center experience. The categorical variables are presented as frequency (percentage) and the continuous variables are presented as median (min-max).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…However, it was not possible to reach higher numbers of such a specific condition with approximately 20% prevalence 3,4,7 in this single-center experience. The categorical variables are presented as frequency (percentage) and the continuous variables are presented as median (min-max).…”
Section: Discussionmentioning
confidence: 70%
“…1,7 The ICG/NIR compatible endoscopic systems were used in all surgeries (Spies Full HD D-Light P ICG technology; Karl Storz, Tuttlingen, Germany for laparoscopic and open surgeries, and da Vinci Xi robotic platform; Intuitive Surgical, California). Briefly, mapped SLNs were resected and any suspicious lymph node was removed regardless of mapping.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This protocol provided a high detection rate (86.1% of overall detection rate and 73% of bilateral detection rate) consistent with other studies using this technique. Overall and bilateral SLN detection rates for ICG are reported between 86-100% and 52-88%, respectively [24][25][26][27][28][29][30][31]. This indicates that there is a short learning curve for the technique as SLNs were reliably detected in this early phase of introducing the ICG and NIFR SLN mapping protocol in our institution.…”
Section: Discussionmentioning
confidence: 70%
“…[35][36][37] NIRS is also widely used in bioassays or the determination of prostate-specific antigen 33 or in immunoassays. 38,39 Due to the advantages of NIRS, such as fast analysis speed, safety, non-destructive assessment of samples, and high accuracy, it can be used to identify benign tumors and cancers by examination of tissues, such as breast cancer, 40 endometrial cancer, 41 gastric cancer, 42 and CRC, 43 by combining NIRS with chemometrics. 44 In a previous study, our research group also found that the characteristic spectra obtained from CRC samples (formalin-fixed, paraffin-embedded) using NIRS could quickly distinguish CRC tissue from normal intestinal mucosa tissue.…”
Section: Introductionmentioning
confidence: 99%